Strength variation characteristics of waste tailings cemented backfill materials with ultrafine particles - Deng, Daiqiang; Wang, Ye; Liang, Yihua; Fan, Jinkuan; Gao, Yu; Ma, Yunfan (Frontiers in Materials, 2023)
In the process of using mine self-produced solid waste to backfill the mine goaf, the difference in backfill materials properties will produce different backfilling effects, which will have a certain impact on the management of the goaf roof, it is particularly important to conduct the material mechanical properties study of the backfill materials in conjunction with the mining method. Through the relevant backfill proportioning ratio test and mechanical property test, the strength variation law of backfill materials under different concentrations and cementation powder addition was analyzed, the results showed that the strength of backfill materials at the age of 7 days with the cement-sand ratio of 1:6, the strength of specimens with 52% and 49% prepared concentrations respectively increased by 1.361 and 1.266 times than that of specimens with 49% and 46% concentrations; for the backfill materials with 49% prepared concentrations and cement-sand ratios of 1:6, 1:9 and 1:12, the specimens strength of the backfill materials with cement-sand ratios of 1:6 and 1:9 was improved by 0.616 MPa and 0.321 MPa, i.e. improved by 109.28% and 114.6% in turn, compared with that of the 1:9 and 1:12 backfill materials when the curing age was 60 days. It can be seen that the amount of cementitious materials added plays a critical function in improving the strength of backfill materials, and in the subsequent application of goaf backfill, the strength of backfill materials can be enhanced by the method of improving the gradation of backfill aggregates and increasing appropriate amount of cementitious materials, so as to achieve the goal of reducing cost and improving the mechanical properties of backfill materials.